Trajectories of working memory and decision making abilities along juvenile development in mice - Thies, Ann Marlene; Pochinok, Irina; Marquardt, Annette; Dorofeikova, Maria; Hanganu-Opatz, Ileana L.; Pöpplau, Jastyn A. (Frontiers in Neuroscience, 2025)
Rodents commonly serve as model organisms for the investigation of human mental disorders by capitalizing on behavioral commonalities. However, our understanding of the developmental dynamics of complex cognitive abilities in rodents remains incomplete. In this study, we examined spatial working memory as well as odor-and texture-based decision making in mice using a delayed non-match to sample task and a two-choice set-shifting task, respectively. Mice were investigated during different stages of development: pre-juvenile, juvenile, and young adult age. We show that, while working memory abilities in mice improve with age, decision making performance peaks during juvenile age by showing a sex-independent trajectory. Moreover, cFos expression, as a first proxy for neuronal activity, shows distinct age-and brain area-specific changes that relate to task-specific behavioral performance. The distinct developmental trajectories of working memory and decision making in rodents resemble those previously reported for humans.